Scaffolds de alginato de sódio adicionados com substâncias naturais melhoram a atividade biológica de células tronco da polpa dentária humana? Uma revisão sistemática com meta-análise - Araújo, Lavina Sousa (2023)
Tissue engineering is an interdisciplinary field that aims to develop techniques to restore the form and function of damaged or lost tissues. In this context, several studies have been conducted with the intention of exploring new materials and cell culturing techniques. As such, this work comprises a systematic review with meta-analysis whose objective was to evaluate, through in vitro studies, the effects of adding natural substances to sodium alginate used as a scaffold for human dental pulp stem cells (hDPSCs). For this purpose, a search was conducted in the PubMed, Lilacs, Scopus, Web of Science, and Embase databases using the descriptors "Stem Cells" and "Alginates," registered in the Medical Subject Headings (MeSH), combined with each other using the Boolean operator "AND," along with their entry terms. Eligibility criteria included in vitro laboratory assays, with no restriction on publication year or language, that utilized natural substances incorporated into sodium alginate and evaluated their effect on hDPSCs. Selection was performed in two stages by two independent blinded reviewers. A total of 14,290 scientific articles were found, and after applying the eligibility criteria, 5 articles were selected to compose this review. All studies presented a low risk of bias. For the meta-analysis, Cohen's d and the 95% confidence interval (CIs) were calculated for cell proliferation assays. A total of 3 studies were included in the meta-analysis (48 samples). There was a significant benefit from the incorporation of natural substances into alginate (Cohen's d of 2.66 [95% CI = 1.27 - 4.05]). Certainty in the body of evidence was evaluated as moderate. Different natural substances were added to alginate to improve its properties, including gelatin, hydroxyapatite, plasma rich in growth factors (PRGF), agarose, nano-hydroxyapatite, growth factors, and lactose-modified chitosan (QTL). The incorporation of hydroxyapatite into alginate induced higher rates of cell proliferation and osteogenic differentiation of hDPSCs. The addition of agarose increased the expression of type 2 collagen and aggrecan. The presence of PRGF promoted higher hDPSC proliferation and elevated osteogenic differentiation. Scaffolds with growth factors exhibited higher cell proliferation. Cell adhesion and osteogenic differentiation were increased in scaffolds with QTL. Therefore, it is concluded that the incorporation of different substances into alginate can contribute to creating a more favorable environment for cell adhesion, proliferation, and differentiation.